(untitled) (Research, Society and Development, 2021)
Objective: to develop an educational technology like a booklet to assist the continuity and transition of care between Primary Health Care and the Outpatient Clinic. Method: This is a methodological, descriptive and exploratory research, with the production of an educational technology aimed at developing a flipbook and audiobook booklet. For the preparation of the content of the booklet, interviews were conducted with 16 nurses who work in the city, which is the scenario for the development of this technology. The interviews were analyzed in terms of content and generated two categories of analysis: the continuity of care for the elderly in Primary Health Care; and strategies identified to enable the continuity of care for the elderly in Primary Health Care. The booklet construction process involved five steps: layout, illustration, writing of texts, content and reference. Result: From the two categories generated with the analysis of the interviews, the chapters of the booklet were structured, comprising: Health Care network; continuity and transition of care; strategies for achieving continuity and transition of care; strategies for achieving continuity and transition of care for the elderly. Conclusion: it is considered that the development of this educational technology helps in the work process in nursing, in health, and in the integration between the health care network.